2012
DOI: 10.1074/jbc.m112.391847
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-2 Desensitizes the Transient Receptor Potential Vanilloid 1 (TRPV1) Channel

Abstract: Background:The TRPV1 receptor is an ionotropic receptor implicated in a variety of pain and inflammatory disorders. Results: ␤-Arrestin-2 scaffolds phosphodiesterase PDE4D5 to TRPV1 to regulate receptor phosphorylation and activity. Conclusion: ␤-Arrestin-2 functions as a scaffold protein to mediate TRPV1 desensitization in multiple cell models. Significance: Our findings presented herein provide compelling support for the contribution of ␤-arrestins as scaffolding proteins in the regulation of ligand-gated io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 61 publications
3
62
0
Order By: Relevance
“…67,77,78 Recent research has demonstrated that β-arrestins are novel regulators that can regulate the function of several TRP channels and desensitize ionotropic receptors. 11,77,79 Por ED et al provided the first evidence that β-arrestin2 regulates TRPV1 receptor through its role as a scaffolding protein. 11 Regulation of TRPV1 by β-arrestin2 induces PKA phosphorylation and effectively desensitizes the ionotropic receptor, which is implicated in a variety of inflammatory and pain conditions.…”
Section: Mor Sensitizes Trpv1 Via β-Arrestin2mentioning
confidence: 98%
See 1 more Smart Citation
“…67,77,78 Recent research has demonstrated that β-arrestins are novel regulators that can regulate the function of several TRP channels and desensitize ionotropic receptors. 11,77,79 Por ED et al provided the first evidence that β-arrestin2 regulates TRPV1 receptor through its role as a scaffolding protein. 11 Regulation of TRPV1 by β-arrestin2 induces PKA phosphorylation and effectively desensitizes the ionotropic receptor, which is implicated in a variety of inflammatory and pain conditions.…”
Section: Mor Sensitizes Trpv1 Via β-Arrestin2mentioning
confidence: 98%
“…8,9 A prominent feature of opioid-induced hyperalgesia is enhanced responsiveness to noxious thermal stimulation, suggesting that transient receptor potential vanilloid type 1 (TRPV1) channels may be an important element of this response. 10 TRPV1 is a nonselective cation (Ca 2+ ) channel that is involved in a variety of nociceptive processes 11 and can be activated by multiple stimuli, including acidic pH (≤ 5.9), noxious heat (> 42°C), endocannabinoids, endogenous lipids, and capsaicin. [12][13][14][15] TRPV1 is widely distributed in the sensory terminals of central and peripheral neurons.…”
Section: Introductionmentioning
confidence: 99%
“…92 Additionally, β-arrestin scaffolding of ubiquitin modulates TRPV4 activation, 93 providing the first example of arrestin-scaffolded regulation of an ion channel. Although TRPV4 has little to do with sensory perception by primary afferent neurons, β-arrestin molecules were also found to target TRPV1 ion channels with scaffolding phosphodiesterase 4D5 (PDE4D5, 94 ). Similar scaffolding of PDE4 by β-arrestin effectively regulates cAMP recruitment following β-adrenergic receptor activation.…”
Section: β-Arrestinmentioning
confidence: 99%
“…In the latter case, a pool of another PDE4D isoform, PDE4D8, is actually released from the ² 1-AR to allow more extensive diffusion of cAMP following ² 1-AR activation. Localised PDE4D5 has also been shown to associate with the 5-hydroxytryptamine receptor [36] and the transient receptor vanilloid 1 (TRPV1) [37] to regulate downstream signalling. Over-expression of dominant negative PDE4D5 constructs increased release of glucagon-like peptide 1 (GLP-1) to influence insulin secretion in enteroendocrine L cells [38].…”
Section: Beta-arrestinmentioning
confidence: 99%